Transformation of marketing strategies in the hospitality industry during the war in Ukraine - Nazymok, Iryna (Запоріжжя: ТДАТУ, 2026)
Political and economic instability caused by the war creates additional for the hotel and restaurant industry. Therefore, adaptation to new conditions and ensuring the financial sustainability of temporary accommodation and catering establishments are becoming urgent needs for representatives of this sector of the economy. In addition, the loss of tourist flows due to active hostilities in the east of the country results in a significant decrease in sales volumes and substantial financial losses, and may threaten the operations of some enterprises [1]. Thus, the problem of the war’s impact on the hotel and restaurant sector is relevant and requires special attention from enterprises in this sector and adaptation to changing environmental conditions. Due to the war, many contracts were disrupted, forcing hotels to seek new, reliable partners [2, p.63].
Keywords: hotel and restaurant industry; marketing